Restoring p53 Function in Head and Neck Squamous Cell Carcinoma to Improve Treatments - de Bakker, Tycho; Journe, Fabrice; Descamps, Géraldine; Saussez, Sven; Dragan, Tatiana; Ghanem, Ghanem; Krayem, Mohammad; Van Gestel, Dirk (Frontiers in Oncology, 2022)
TP53 mutation is one of the most frequent genetic alterations in head and neck squamous cell carcinoma (HNSCC) and results in an accumulation of p53 protein in tumor cells. This makes p53 an attractive target to improve HNSCC therapy by restoring the tumor suppressor activity of this protein. Therapeutic strategies targeting p53 in HNSCC can be divided into three categories related to three subtypes encompassing WT p53, mutated p53 and HPV-positive HNSCC. First, compounds targeting degradation or direct inhibition of WT p53, such as PM2, RITA, nutlin-3 and CH1iB, achieve p53 reactivation by affecting p53 inhibitors such as MDM2 and MDMX/4 or by preventing the breakdown of p53 by inhibiting the proteasomal complex. Second, compounds that directly affect mutated p53 by binding it and restoring the WT conformation and transcriptional activity (PRIMA-1, APR-246, COTI-2, CP-31398). Third, treatments that specifically affect HPV+ cancer cells by targeting the viral enzymes E6/E7 which are responsible for the breakdown of p53 such as Ad-E6/E7-As and bortezomib. In this review, we describe and discuss p53 regulation and its targeting in combination with existing therapies for HNSCC through a new classification of such cancers based on p53 mutation status and HPV infection.